0312 Sleep and fear of falling, is there a relationship? A cross-sectional study in older adults. (25th May 2022) - Kakazu, Viviane; Andersen, Monica; Pinto, Rafael; Dokkedal-Silva, Vinícius; Fernandes, Guilherme; Gobbi, Cynthia; Tufik, Sergio; Pires, Gabriel; Morelhão, Priscila
Abstract: Introduction: Excessive daytime sleepiness is a common problem in older people. This population is at higher risk of falls that lead to injuries, which explains the high prevalence of fear of falling among them. The relationship between sleep disturbances and concern about falling is unclear. The aim of this study was to identify whether poor sleep quality and excessive daytime sleepiness are associated with fear of falling in older adults. Methods: This is a cross-sectional study. Data on age, sex, body mass index, alcohol consumption, mental status, depression, single-leg stance, excessive daytime sleepiness (Epworth Sleepiness Scale), sleep quality, comorbidities, and fear of falling (assessed through the Falls Efficacy Scale), were collected from participants aged 60 years and over. Univariable and multivariable linear regression were performed. Logistic regression evaluated the association between excessive daytime sleepiness and high fear of falling. Results: 504 participants were analyzed. The chance of an older person having high concern of falling was 3 times bigger among those with excessive daytime sleepiness when compared to those without excessive daytime sleepiness. The final model, multivariable linear regression showed that excessive daytime sleepiness score was able to predict fall efficacy scale scores (Beta coefficient=0.26; 95%CI: 0.07 to 0.45) adjusted by the following variables: age, single-leg stance, comorbidities, and depression. Our results showed that for each point increase on the Epworth Sleepiness Scale there was an average increase of 0.26 points in the Falls Efficacy Scale, indicating that sleepiness was related to fear of falling. Conclusion: Having excessive daytime sleepiness increased the chance of older adults showing a high fear of falling. Healthcare workers should be aware that drowsiness can increase the fear of falling among older patients, and this may influence treatment. Support (If Any): The study was supported by Associação Fundo de Incentivo à Pesquisa (AFIP) and Coordenação de Aperfeiçoamento de Nível Superior (CAPES, Finance Code 001 to GLF). ST, MLA and RZP received fellowships from Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq). GLF receives funding from CNPq (#141445/2021-1)